2008
DOI: 10.1016/j.cell.2008.10.017
|View full text |Cite
|
Sign up to set email alerts
|

The Autistic Neuron: Troubled Translation?

Abstract: Autism is a complex genetic disorder, but single-gene disorders with a high prevalence of autism offer insight into its pathogenesis. Recent evidence suggests that some molecular defects in autism may interfere with the mechanisms of synaptic protein synthesis. We propose that aberrant synaptic protein synthesis may represent one possible pathway leading to autistic phenotypes, including cognitive impairment and savant abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
515
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(551 citation statements)
references
References 63 publications
24
515
0
3
Order By: Relevance
“…Furthermore, neuronal dysfunctions are due to the modifications in synthesis level of synaptic proteins caused by a defective mRNA regulation especially translation (Kelleher & Bear, 2008). This mechanism is controlled by several genes in particular mTOR and FMR1 .…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, neuronal dysfunctions are due to the modifications in synthesis level of synaptic proteins caused by a defective mRNA regulation especially translation (Kelleher & Bear, 2008). This mechanism is controlled by several genes in particular mTOR and FMR1 .…”
Section: Reviewmentioning
confidence: 99%
“…This mechanism is controlled by several genes in particular mTOR and FMR1 . FMRP protein, encoded by FMR1 gene, binds to 400 different mRNAs and represses their translation (Kelleher & Bear, 2008). The loss of FMRP protein results in fragile X syndrome that is present in 5% in patients with ASD.…”
Section: Reviewmentioning
confidence: 99%
“…Recently, whole-exome studies have reported an enrichment of FMRP-associated genes in the lists of genes disrupted by RVs in ASD participants [23]. FMRP is associated with the autism candidate genes MET [116], PTEN , TSC1 , TSC2 and NF1 [117], which are also located within the PSD [118-120]. These genes are part of the phosphatidylinositol 3-kinase (PI3K)-AKT-mTOR pathway which is activated by metabotropic glutamate receptor signaling [119,121], is an upstream effector of translation regulation, and is involved in cellular proliferation [122].…”
Section: Emerging Biological Themesmentioning
confidence: 99%
“…5 Therefore, dysfunctional mTORC1 signaling and dysregulated protein synthesis in neuronal cells have been associated with several neurodevelopmental disorders with intellectual disability and autism. [6][7][8][9][10][11] mTORC1 signaling modulates assembly of the translation initiation machinery by interacting with the eukaryotic initiation factor eIF3, a scaffold complex that brings all components of the translation initiation process into close proximity, and by coordinating the phosphorylation and activity of key translational regulators S6K1 and 4EBP1. 12 We have recently identified two novel binding partners for eIF3, the neural Rho-GEF collybistin (CB) and the synaptic scaffold protein gephyrin, 13 which are known to be required for GABA A receptors clustering and inhibitory synapse formation.…”
Section: Introductionmentioning
confidence: 99%